Psychology applied to work : an introduction to industrial and organizational psychology - Muchinsky, Paul M. (Wadsworth Pub, 2000)
From important new issues such as antisocial behavior in the workplace, reorganization and downsizing, work stress, and cultural diversity training, to key topics such as job satisfaction, this book offers information and practical insights to understand this quickly evolving field. Using real company examples throughout the book, the author consistently relates on-the-job situations to the best practices offered by industrial and organizational psychology. Key updates and enhancements throughout this 6th edition help readers understand the social, cultural, and structural changes affecting business and the workplace, as well as their impact on employers and employees. Other topics covered include cross-cultural issues as they relate to specific key topics in industrial/organizational psychology, job attitudes, emotional intelligence, societal changes in affirmative action, and 360-degree feedback.